Tunable sinusoidal oscillator using CCII with variable current gain - Kumngern, Montree; Phatsornsiri, Punnavich; Dejhan, Kobchai (My University, 2013)
This paper presents a new electronically tunable sinusoidal oscillator. The proposed oscillator is consisted of two second-generation current conveyors with variable current gain, two grounded capacitors, one grounded resistor and one floating resistor. Unlike previously oscillators, the condition and the frequency of oscillation of this oscillator can be controlled electronically and independently by adjusting the current gains of current conveyors. The proposed circuit is beneficial to monolithic integrated circuit implementation using only grounded capacitors. Simulation results that confirm the theoretical predictions are also given. © 2013 IEEE.
Keywords: analogue circuit; second-generation current conveyor; sinusoidal oscillator